Modeling and simulation in pediatric drug therapy: Application of pharmacometrics to define the right dose for children. Issue 3 (20th July 2015) - Vinks, AA; Emoto, C; Fukuda, T
<x xml:space="preserve">Abstract</x> During the past decades significant progress has been made in our understanding of the importance of age‐appropriate development of new drug therapies in children. Importantly, several regulatory initiatives in Europe and the US have provided a framework for a rationale. In the US, most notably the enactment of the Best Pharmaceuticals for Children Act (BPCA) and Product Research and Equity Act (PREA) has facilitated the studying of on‐patent and off‐patent drugs in children. The biggest challenge in pediatric studies is defining a safe and effective dose or dose range in a patient population that can span from premature neonates to adolescents. From a mechanism‐based perspective, advances in the science of quantitative pharmacology and pharmacometrics have resulted in the development of model‐based approaches to better describe and understand important age‐related factors influencing drug disposition and response in pediatric patients. The application of modeling and simulation has been shown to result in better estimates of pediatric doses as evidenced by several studies, although the optimal approach is still being debated. The extrapolation of efficacy findings from adults to the pediatric population has streamlined the development process especially for studies in older children. However, a focus on developmental changes in neonates and infants as well as further developing a paradigm for conducting pharmacodynamic studies in neonates, infants, and children remain important unmet needs. In this overview we will review current approaches for age‐appropriate dose selection and highlight ongoing efforts to define exposure–response and clinical outcome relationships across the pediatric age spectrum.